INCIDENCE OF NEW-ONSET ATRIAL FIBRILLATION IN PATIENTS WITH AND WITHOUT HYPERURICEMIA (Journal of Medical & Health Sciences Review, 2025)
Background: Hyperuricemia has been increasingly linked to cardiovascular diseases, yet its association with new-onset atrial fibrillation (AF) remains unclear.Objective: To determine the incidence of new-onset atrial fibrillation in patients with and without hyperuricemia and assess whether hyperuricemia independently predicts AF development. Methods: This prospective cohort study was conducted at Fauji Foundation Hospital, Lahore from 1st Oct 2024 to 5 April 2025. A total of 189 adult patients aged 18 years and above were enrolled in the study. Baseline demographic data including age, sex, body mass index (BMI), and comorbidities such as hypertension, diabetes mellitus, and smoking status were recorded. Laboratory tests including serum uric acid, creatinine, and lipid profile were documented at the time of enrollment.Results: Out of the 189 patients, 94 (49.7%) had hyperuricemia. Atrial fibrillation developed in 19 patients (20.2%) in the hyperuricemia group and in 7 patients (7.4%) in the normouricemia group (p = 0.01). Kaplan-Meier analysis showed a significantly higher cumulative incidence of AF in the hyperuricemic group (log-rank p = 0.008). In multivariable Cox regression, hyperuricemia was independently associated with increased risk of new-onset AF (hazard ratio 2.73; 95% CI: 1.15–6.49; p = 0.023), along with age >65 years and hypertension. Conclusion: It is concluded that hyperuricemia is significantly associated with an increased risk of new-onset atrial fibrillation. Serum uric acid may serve as a useful biomarker for AF risk stratification. Further studies are warranted to determine whether urate-lowering therapies could play a preventive role in atrial fibrillation development.